Kinetic and simulation studies of the esterification of acrylic acid with 2- ethyl hexanol in a batch and packed bed reactor - Mohd Amirul Asyraf, Ahmad (2020)
Wastewater containing acrylic acid (AA) imposes detrimental effect to the environment due to its high value of chemical oxygen demand. Recovery of AA from its dilute aqueous solution for heterogeneously catalysed esterification in a reactive distillation column (RDC) could be a promising approach. Typically, the feasibility study of these intensified processes was carried out in batch process to determine the reaction kinetics. It is insufficient to determine the other important fundamental data such as mass transfer and mixing which are also crucially required during the equipment design. This consideration is important to observe the probability of underperformance due to the problems such as incomplete catalyst wetting, severe mass-transfer resistances, or maldistribution. In the present study, the investigation on the suitable heterogeneous IER catalyst and appropriate operating window for the esterification reaction to recover AA from the wastewater was conducted. The fundamental data includes reaction kinetics, mass transfer and mixing for simulate, design, and construction of the intensified RDC and CR for the recovery of AA from the wastewater would also be obtained. The continuous flow tubular packed bed reactor (PBR), a system mimicking the reactive section in the intensified processes was used. The best sulfonic acid functional cation-exchange resin catalysts, SK104, SK1B, PK208, PK216, PK228, RCP145, and RCP160, were screened in a batch system. PK208 outperformed the other resins and it was used in subsequent studies. Eley-Rideal (ER) was the best kinetic model to correlate the production rate of 2EHA. Endothermicity of the AA esterification with 2EH was indicated by the increase of its equilibrium constant with temperature. The critical factor that contribute toward reaction performance include initial concentration of acrylic acid (AA), temperature, molar ratio of reactant (AA and 2EH), catalyst loading, and polymerisation inhibitor loading was studied using 2 factorial designs. Initial concentration of AA and temperature was found affected the esterification of AA with 2EH the most. Since the contribution of additional polymerisation inhibitor loading was not significant, this factor has been neglected to be studied in further experiment. The existing amount of the polymerisation inhibitor contained in raw AA is sufficient to avoid AA polymerisation. Residence time distribution (RTD) was studies to examine the mixing behavioural of system. Due to the severe channelling occurred, catalyst cage need to be install. An adsorption study using nonreactive binary mixtures was performed to observe the affinity of resin against each compound. The affinity of PK208 resin towards the chemical species involved in 2EHA synthesis in descending order is: water> AA> 2EH/2EHA. Catalytic performance of resin PK208 for the esterification between acrylic acid (AA) and 2-ethyl hexanol (2EH) was then evaluated in packed bed reactor (PBR) under various temperatures (55-90⁰C), catalyst loadings (1-15 g), molar ratios of AA to 2EH (1:1-1:5), and feed flow rates (1-5 ml/min). The best condition that gave highest yield, 66.44mol% was at 95 ⁰C, with catalyst loading of 5 g, molar ratio AA:2EH of 1:3, and feed flow of 1 ml/min. In contrast to the batch system, the effect of initial concentration of AA was found to be not significant anymore. The PBR simulation performed using plug flow reactor model showed that the predicted results deviated marginally from the experimental data, owing to the occurrence of dispersion in PBR as proven by the residence time distribution (RTD) study. The PBR experimental data well matched with the simulation results generated from the packed bed reactor model considering the axial dispersion in PBR. Thus, the identified operating window and fundamental data validated the potential of RDC in converting the AA in wastewater with the better efficiency.